Both children and adult patients with difficult‐to‐treat atopic dermatitis have high prevalences of concomitant allergic contact dermatitis and are frequently polysensitized. (30th April 2018) - Boonstra, M.; Rustemeyer, T.; Middelkamp‐Hup, M.A.
Abstract: Background: Concomitant allergic contact dermatitis (ACD) has been described as a possible cause of atopic dermatitis (AD) becoming difficult‐to‐treat. However, contact sensitization in this patient group has barely been studied. Objective: To study the occurrence of ACD in a population of difficult‐to‐treat AD children and adults. Methods: Clinical and patch test information of 48 patients with difficult‐to‐treat AD unresponsive to conventional outpatient treatments was gathered retrospectively. We studied prevalence and relevance of common allergens, performed dynamic patch test analysis and assessed occurrence of polysensitization. Results: In 48 patients with difficult‐to‐treat AD, 75% ( n = 36/48) had a concomitant contact allergy, and 39% ( n = 14/36) of these patients were polysensitized. ACD and polysensitization prevalences were equal amongst children and adults. The most frequent and relevant reactions were seen against wool alcohols, surfactants cocamidopropyl betaine and dimethylaminopropylamine, bichromate and fragrance mix I. Dynamic pattern analysis showed these reactions to be mostly allergic and not irritative of nature. Conclusion: Difficult‐to‐treat AD patients frequently suffer from concomitant (multiple) contact allergies, and this may be a reason why the AD turns into a difficult‐to‐treat disease. Awareness of this phenomenon is necessary, as pragmatic implementation of allergen avoidance strategies may be helpful in getting disease control in this population.